Analisis Kesulitan Siswa dalam Menyelesaikan Soal Cerita pada Materi Teorema Pythagoras - Nurmayunita, Nurmayunita; Soeprianto, Harry; Junaidi, Junaidi; Patmi, Sri (Griya Journal of Mathematics Education and Application, 2024)
This research aims to describe the difficulties experienced by students at SMP Negeri 8 Mataram in solving word problems on the Pythagorean Theorem. This research is a mix method. The instruments in this research are test instruments and interview guidelines. Data analysis techniques use quantitative and qualitative data analysis techniques. The result shows that (i) The majority of students (90%) had difficulty understanding the problems in the Pythagorean Theorem in the form of word problems, (ii) 60% had difficulty planning a solution, especially in illustrating pictures that support understanding the questions and some students had difficulty determining the formula. used, (iii) Difficulty implementing the solution plan by 50%, especially students having difficulty in the calculation process, especially when calculating roots, (iv) Difficulty re-checking the solution results by 65%, this includes students' lack of habit in drawing conclusions and re-checking to the solution results.